Implementation of virtual reality based treatment of motor disorders in children with cerebral palsy - Stanisavljević, Saša; Nedović, Goran (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Virtual reality is a computer-generated interactive simulation of reality that provides a wide range of possibilities for creating a beneficial therapeutic program. The use of virtual reality systems in the rehabilitation of motor disorders in children with cerebral palsy is relatively recent. Objective. Accordingly, the aim of this review is to establish the level of effectiveness of rehabilitation interventions based on virtual reality systems in the treatment of children with cerebral palsy, based on the available literature. Methods. The initial search identified 63 scientific papers (research reports). By applying the selection criteria, nine papers were selected that met the given criteria and thus entered the further process of analysis. During the analysis, special attention was paid to: the outcomes of therapeutic procedures (the achieved results); and the analysis of the selection criteria of virtual reality systems to be used in the rehabilitation and accessibility of these systems for commercial and clinical applications. Results. Contradictory results have been found based on the analysis of the levels of effectiveness of rehabilitation interventions. In addition to studies that testify to the unequivocally positive effects of the application of virtual reality in the rehabilitation of children with cerebral palsy, there are also those in which it is evident that this effect is absent. Conclusion. The general conclusion of this paper is that virtual reality systems have great potential for application in the field of rehabilitation of motor disorders, but also that this area is still not sufficiently researched and requires further engagement to go one step further to justify or challenge their application.